Keragaman Jenis Tumbuhan Obat Di Hutan Pendidikan Universitas Sumatera Utara Kawasan Taman Hutan Raya Tongkoh Kabupaten Karo Sumatera Utara - Eva Friska Br Sembiring; Indriyanto Indriyanto; Duryat Duryat (Department of Forestry, Faculty of Agriculture, University of Lampung, 2015)
Tongkoh Great Forest Park has an excellent site factor for various types of medicine plants. The research about the medicine plants spesies diversity in Tongkoh Great Forest Park was needed because there was the lack of information about the types of medicine plants in the area. The purpose of the study was to determine the diversity of species and it's abundance, in the area of utilization block area Tongkoh Great Forest Park, Karo District, North Sumatra Province. This research was conducted on August 2014 in the utilization area of Tongkoh Great Forest Park, Karo District, North Sumatra Province by inventory method was employed using the terraced lines method that arranged systematically and started with purposive sampling, based on the presence of medicine plants that had known by local communities in around area. The distance between the pioneer lines were 200 m and the distance between the plots and the path lines were 100 m. The results of the research show that there are 25 species of medicine plants which are divided into 21 families. The most dominant species was pegagan (Centella asiatica) with density about 9,500 individu/hectare and frequency at 0.26 and tree species which have the highest relative density was pine (Pinus merkusii) with frequency was 0.2 and the density was 60 individu/hectare. Keywords: medicinal plants, diversity